Focus on comprehension - Green, Mary (Learners Publishing, 2006)
This book contains approximately 35 passages, with focused comprehension tasks that are preceded by the teaching of key comprehension skills. There are 21 main units, each dealing with a particular skill or area, and 4 summative Pratice Units and a final Assessment Paper, all designed to prepare students for formal assessments.